Emergencies in psychiatry in low- and middle-income countries : second edition - Rangaswamy, Thara; Vijayakumar, Lakshmi (Boca Raton, FL : CRC Press, 2017)
"There is a need to not only understand psychiatric emergencies in low- and middle-income countries but also to formulate logical and acceptable forms of intervention. This book gives the reader an overview of the kinds of psychiatric emergencies that can occur and the strategies employed to manage these in developing countries. The book covers anxiety disorders, psychotic disorders, personality disorders, substance abuse disorders, grief, suicidal behaviour and psychiatric emergencies following disasters. It also deals with special population groups, such as women, children and the elderly, who require different modes of intervention."--Provided by publisher.
chapter 1 Anxious Patient in the Emergency Ward -- chapter 2 Psychiatric Emergencies in Substance Abuse -- chapter 3 Psychotic Disorders including Schizophrenia -- chapter 4 Psychiatric Emergencies in Grief -- chapter 5 Emergency Treatment of the Acutely Disturbed and Aggressive Patient -- chapter 6 Psychiatric Emergencies Associated with Drug Overdose -- chapter 7 Psychiatric Emergencies in Women -- chapter 8 Emergency Management of Suicidal Behavior -- chapter 9 Psychiatric Emergencies in Disaster Situations -- chapter 10 Child Psychiatric Emergencies -- chapter 11 Sexual Emergencies: A Psychiatrist$1 (Bs Perspective -- chapter 12 Psychiatric Emergencies in Medical Conditions -- chapter 13 Psychiatric Emergencies in Personality Disorders -- chapter 14 Legal Aspects of Psychiatric Emergencies -- chapter 15 Psychiatric Emergencies in the Elderly -- chapter 16 Psychiatric Emergencies after Terrorist Attacks.s
Includes bibliographical references.
Keywords: Psychiatric emergencies; Crisis intervention (Mental health services); Psychiatry